Nucleos(t)ide analogue cessation outcomes in non-cirrhotic patients with HBeAg-negative chronic hepatitis B - Ellik, Zeynep Melekoglu; Unal, Fatma Tugce Sah; Koc, Oezge; Duman, Serkan; Guvenir, Sevinc Tugce; Yilmaz, Volkan; Idilman, Ramazan (Elsevier, 2025)
[Abstract Not Available]
European-Association-for-the-Study-of-the-Liver Congress -- MAY 07-10, 2025 -- Amsterdam, NETHERLANDS